Interaction of basal forebrain cholinergic neurons with the glucocorticoid system in stress regulation and cognitive impairment - Paul, Saswati; Jeon, Won Kyung; Bizon, Jennifer L.; Han, Jung-Soo (Frontiers in Aging Neuroscience, 2015)
A substantial number of studies on basal forebrain cholinergic neurons (BFCN) have provided compelling evidence for their role in the etiology of stress, cognitive aging, Alzheimer’s disease (AD), and other neurodegenerative diseases. BFCN project to a broad range of cortical sites and limbic structures, including the hippocampus, and are involved in stress and cognition. In particular, the hippocampus, the primary target tissue of the glucocorticoid stress hormones, is associated with cognitive function in tandem with hypothalamic-pituitary-adrenal (HPA) axis modulation. The present review summarizes glucocorticoid and HPA axis research to date in an effort to establish the manner in which stress affects the release of acetylcholine, glucocorticoids, and their receptor in the context of cognitive processes. We attempt to provide the molecular interactive link between the glucocorticoids and cholinergic system that contributes to BFCN degeneration in stress-induced acceleration of cognitive decline in aging and AD. We also discuss the importance of animal models in facilitating such studies for pharmacological use, which could help decipher disease states and propose leads for pharmacological intervention.